THE REINTERPRETATION OF THE FORMULAS OF THE PAST: IL CIRCO BY ISIDORA ŽEBELJAN IN THE POETIC AND THEORETICAL-ANALYTICAL INTERPRETATION (Heritage, 2025)
Il Circo (1993) by Isidora Žebeljan, the piece inspired by Nino Rota’s music for the movie The eight and a half (1963), is significant because it prejudges the distinctive aspects of the composer’s musical expression. With а strong, creatively recognizable impulse, the piece flirts with the cultural heritage of the past, multiple entering into its clearly defined patterns – which in a new constelation become the provocative subjects of the new meaning. In the intrinsic game of the formula of the past, Žebeljan provokes the basis of the established meanings, lucidly reinterpreting them through several points: by using a musical quote, associating to the mechanical piano, by a genre of the romantic miniature, by easily noticeable formal pattern whose architectural princip of construction immanently „defies“ itself, by contemporary musical expression which rests on the formulas of the past – romantic, but also on the harmonic idiom of classicism and specific postmodernist gestures. In a kind of hypertext form, the piece gets meaning of the double variations – according to the subject of his creative replika, but also according to the way of „sprouting“ the matter itself.
Keywords: Isidora Žebeljan, Il Circo, reinterpretation, variation, the formulas of the past, poetics.